Influence of fiber diameter and crystallinity on the stability of electrospun poly(L-lactic acid) membranes to hydrolytic degradation - Dias, J. C. (2012)
Hydrolytic degradation of electrospun mats of poly(L-lactic acid), PLLA, as a function of crystallinity and fiber diameter has been studied. The degradation in a saline phosphate buffer solution (PBS) up to 20 weeks produced a slight decrease in the sample mass but a clear decrease of the polymer average molecular weight in the amorphous fibers. The aforementioned effect decreases as crystallinity increases. Important for applications is that morphological characteristics of the membranes such as average fiber diameter and membrane porosity are also affected by the degradation process. Fiber diameter increases while membrane porosity decreases, resulting in closer packed fibers due to the release of internal tensions related to the electrospinning and/or thermal treatment processes.